The Relationship of Student Learning Motivation Against Student Learning Independence on Dynamic Electric Material - Dina fajrin; Dwi fajar saputri; Ira Nofita Sari (Program Studi Pendidikan Fisika FKIP Universitas Lambung Mangkurat, 2021)
This study analyses the relationship between student' learning motivation and student learning independence on dynamic electrical material in class IX SMP Negeri 7 Sungai Raya. The research method used is descriptive, with a correlative form of research. The population is 117 student from all grade IX students of SMP Negeri 7 Sungai Raya, the sample used in this study was 89 students. The sampling technique uses simple random sampling. Values used for independent and bound variables use a questionnaire. The Values analysis technique used is descriptive statistics and correlations with the coefficient of determination at a significant level of 5%. The result of research found that (1) student motivation in class IX SMP Negeri 7 Sungai Raya in the good category; (2) the independence of student learning was in a good category;  and (3) there was a positive and significant relationship between student motivation on student learning independence. So it can be concluded that the greater the student's learning motivation, the greater their learning independence.